Estimating ŋ/s of QCD matter at high baryon densities. (January 2016) - Karpenko, Iu.; Bleicher, M.; Huovinen, P.; Petersen, H.
Abstract: We report on the application of a cascade + viscous hydro + cascade model for heavy ion collisions in the RHIC Beam Energy Scan range, √snn = 6.3…200 GeV. By constraining model parameters to reproduce the data we find that the effective (average) value of the shear viscosity over entropy density ratio ŋ/s decreases from 0.2 to 0.08 when collision energy grows from √sNN ≈ 7 to 39 GeV.